RELATIONSHIP OF SNP (RS867500) STX1A EXON 10 GENE WITH INTELLECTUAL INTELLIGENCE LEVEL - Qur'andini, Dalinur; Yuwono, Yuwono; Triwani, Triwani (Biomedical Journal of Indonesia, 2019)
The purpose of this study was to determine the relationship of SNP (rs867500) on the STX1A Exon 10 gene with the level of intellectual intelligence. This study was an observational analytic study with a cross sectional study design with a population of 368 and a sample of 36 which was divided into two groups, namely the above average IQ group and the average IQ group. To find out the relationship of SNP (rs867500) STX1A Exon 10 gene with intelligence level used X2 test (Chi-square). The results showed no SNPs were found in the STX1A exon 10 gene. The STX1A gene can be said to contribute to intelligence along with other genes, namely IGFR2 and FNBPL1 genes, although there is no polymorphism in the exon 10 STX1A gene.